2020
DOI: 10.1080/09638237.2020.1714002
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of factors influencing the implementation of group psychoeducational initiatives for people experiencing mental health difficulties and their families

Abstract: Background: Despite evidence to support the effectiveness of psychoeducation for people experiencing mental health difficulties and their families, understanding issues around the implementation of such programmes is limited. Aim: The aim of this scoping review was to synthesise the peer-reviewed literature on barriers and enablers influencing the implementation of group psychoeducation in adult mental health services. Methods: Using a pre-defined search strategy and PRISMA guidelines, four databases were syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
(201 reference statements)
0
7
0
Order By: Relevance
“…The implementation of any complex intervention and transition from initial adoption to routine practice is "a nonlinear process characterized by setbacks and unanticipated events" [13 p. 610). Similar to other studies, the e cacy of the intervention was cited to be a critical facilitator to implementation [30]. The intervention's rigorous development, piloted feasibility, tested e cacy, and evidence-based handbooks convinced many stakeholders of its value.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The implementation of any complex intervention and transition from initial adoption to routine practice is "a nonlinear process characterized by setbacks and unanticipated events" [13 p. 610). Similar to other studies, the e cacy of the intervention was cited to be a critical facilitator to implementation [30]. The intervention's rigorous development, piloted feasibility, tested e cacy, and evidence-based handbooks convinced many stakeholders of its value.…”
Section: Discussionmentioning
confidence: 69%
“…While the inclusion of multiple sites and different cohorts of stakeholders provided a triangulated and deepened understanding of factors in real-world settings [10,[59][60][61] and thus addressed some of the methodological issues identi ed in previous studies [30], there are several limitations that need to be acknowledged. First the self-selection nature of the sample may have resulted in recruitment bias, with those who were more assertive, con dent, and articulate and with strong views opting to participate.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of any complex intervention and transition from initial adoption to routine practice is "a nonlinear process characterized by setbacks and unanticipated events" [13 p. 610]. Similar to other studies, the e cacy of the intervention was cited to be a critical facilitator to implementation [34]. The intervention's rigorous development, piloted feasibility, tested e cacy, and evidence-based handbooks convinced many stakeholders of its value.…”
Section: Discussionmentioning
confidence: 85%
“…Despite the strength of the evidence-base in relation to psychoeducation [19][20][21][22][23][24], and its successful integration into policy recommendation and clinical guidelines [25][26][27][28], equitable access for many service users and family members has still not been achieved [29]. Alongside nascent research exploring the implementation determinants of one to one psychoeducation [30][31][32][33], a recent scoping review [34] reported some participant, practitioner, intervention, organisational and structural barriers and facilitators to group psychoeducation. While the review provided useful insights, the authors noted several methodological limitations of the included studies which restrict the generalisability of their ndings, including heterogeneity of study design and a narrow focus on one stakeholder perspective and one site of implementation.…”
Section: Introductionmentioning
confidence: 99%